Use practices and profile of microbiological contamination of lab coats in medical school - Scheidt, Katia Liberato S.; Ribeiro, Rachel L.; Araújo, Augusto Righetti V. F. de; Chagas, Geórgia Marielle S.; Carneiro, Marianna S.; Canuto, Rubens; Corbelli, Camila Cecilia O. (Medicina (Ribeirao Preto), 2015)
The coats are a potential microbiological transmission means and its misuse brings risks to health professionals and population. The goal of this study was to know the usage practices and the profile of contamination of the smock worn by professors and students of the University Center Serra dos Órgãos (UNIFESO). It is a quantitative study, cross-sectional and exploratory. Respecting ethical principles, a questionnaire on the use of the white coat was applied and the microbiological analysis was held. The data were analyzed manually, expressed in percentages and demonstrated through tables. As a result, 73 (seventy-three) coats studied showed varied flora and predominance of Gram-positive cocci. The region of the wrist, the most contaminated, presented a UFC 23 average per field. As for the usage profile, the majority, 42, (57%) are between the ages of 18 and 25 years, 46 (63%) are female, 32 (44%) are medical students in the 3rd term and only 13 (18%) are professors. On the frequency of changing of lab coat, 35 (48%) change it once a week, however with inappropriate handling. After use, 36 (49%) do not wash the coat separately, 43 (58%) do not use disinfectant products, 54 (73%) use ironing as an additional measure against microbiological contamination. It is concluded that there is imperious need for awareness of scholars and professors of appropriate use/handling of the lab coat and the importance of clothing in the epidemiology of infections intra/extra health care environment.